Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1537-2995.2005.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Is an assay for simultaneous detection of hepatitis C virus core antigen and antibody a valuable alternative to nucleic acid testing?

Abstract: This new developed assay presents an improvement for the detection of HCV infection, especially in the early phase of infection when antibodies are undetectable. Although less sensitive than NAT, this assay could be a suitable solution for blood screening in developing countries where NAT (or HCV core antigen-specific assay) is not affordable or its implementation is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 42 publications
3
52
1
2
Order By: Relevance
“…Nevertheless, these long intervals are those observed in the "real" clinical setting and in the management of HIV-infected patients. Of note, our detection delays are consistent with those previously calculated with either commercial (30 days) or so-called natural (28 days) seroconversion panels (2,10). Importantly, for a majority of patients, the combined assay became positive as early as HCV RNA detection.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, these long intervals are those observed in the "real" clinical setting and in the management of HIV-infected patients. Of note, our detection delays are consistent with those previously calculated with either commercial (30 days) or so-called natural (28 days) seroconversion panels (2,10). Importantly, for a majority of patients, the combined assay became positive as early as HCV RNA detection.…”
supporting
confidence: 88%
“…The simultaneous detection of both antigen and antibody (Ab) is now commonly used for the diagnosis of human immunodeficiency virus (HIV) infection, with the result being a dramatic shortening of the so-called seronegative window and, subsequently, the earlier diagnosis of recent infection. A similar approach based on the HCV core protein and specific anti-HCV antibody detection (Monolisa HCV Ag-Ab Ultra; Bio-Rad Laboratories, Marnes-la-Coquette, France) has recently been developed for the diagnosis of hepatitis C. The overall performance of this combined assay has previously been evaluated with seroconversion panels and HCV RNA-positive HCV Ab-negative samples (2,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not assume the treatment at cirrhosis in our model. Second, our screening strategy contained the HCV core antigen test, which has been recently recommended for use in screening because of the cheaper price and the easier performance in comparison to the HCV-PCR test (Bouvier-Alias et al 2002;Laperche et al 2005). Third, the combination therapy with peginterferon plus ribavirin has replaced interferon in combination to ribavirin which was used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth-generation assay was reactive a mean of 21.6-26.0 days before thirdgeneration assays. 186,187 Fourth-generation assays were reactive a mean of 4.8-30.0 days after NAT. 187,188 One study reported a turnaround time of 190 minutes to perform the test.…”
Section: Hcv Fourth-generation Immunoassays This Reviewmentioning
confidence: 99%